Database encrytion schemes : a comparative study - Zailani Mohamed Sidek, Assoc.Prof.Dr.; Norbik Bashah Idris; Harihodin Selamat; Conference on Information Technology Research and Applications (2002 : UNITAR, Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2002)
57